Peningkatan Hasil Belajar Matematika melalui Metode Gogo Iwac pada Siswa Kelas VIII SMP Negeri 1 Plumpang - Subekti Wahono; Yuliana Mustikawati; Tulus Widodo; Widodo Hery Susanto (PGRI Provinsi Jawa Timur, 2023)
This research aims to examine the improvement in mathematics learning outcomes through the implementation of the Gogo Iwac method (Google Classroom and Google Forms for Individual Work Activity). The study was conducted at SMP Negeri 1 Plumpang, with eighth-grade students in Semester II as the research subjects. The research employed a Classroom Action Research approach consisting of two cycles. Data collection involved both test and non-test instruments, and data analysis was conducted by analyzing the learning outcomes from the Pre-Cycle, Cycle I, and Cycle II. The results of the study indicate a significant increase in the average scores from 66.39 in the Pre-Cycle to 71.25 in Cycle I, and further to 82.64 in Cycle II. This is also reflected in the graphical representation of the percentage of students’ mastery of the material. While the Pre-Cycle percentage of mastery was only 33.3%, it increased to 52.8% in Cycle I, and in Cycle II, it significantly rose to 94.4%, indicating that the students have achieved mastery in the topic of spatial figures in a classical sense. These findings demonstrate that the Gogo Iwac method can enhance student learning outcomes in mathematics. The implications of this research suggest the effectiveness of integrating technology tools like Google Classroom and Google Forms for individual work activities to improve mathematics learning outcomes. Further research is recommended to explore the long-term impact and scalability of the Gogo Iwac method in different educational settings.